The Distinction Between Normal and Deviant - Stevanović, Zoran (Zbornik Instituta za kriminološka i sociološka istraživanja, 2013)
The distinction between normal and deviant-abnormal is a time-consuming project that is carried out, refining and changing. Unfortunately, its heterogeneity and consensual disharmony are represented quite vaguely and unstably scientifically, which makes it hard to be objective and precise when determining the line between normal and pathological. A great number of authors claim that there will not be one final definition of abnormality, but there is a concurrence that defining pathology will vary depending on the time, culture, values and moral norms, etc. Normal behaviour is characterised by: emotional stability and maturity, developed social skills and average intelligence, realistic ability to assess skills and possibilities, and the ability to establish qualitative interpersonal relations with others. Continued presence of characteristics contrary to the above is considered to be a sign of abnormality-deviance.